2023
DOI: 10.1111/opn.12578
|View full text |Cite
|
Sign up to set email alerts
|

‘I don't want to impose on anybody’: Older people and their families discuss their perceptions of risk, cause and care in the context of falls

Lucille Kerr,
Paula Newman,
Philip Russo

Abstract: BackgroundFalls in hospitalised patients remain an ongoing challenge for healthcare systems internationally. Limited research exists on the perspectives of older people on falls risk, cause and care.ObjectivesThis study explored the experiences of patients and their families after a fall in a healthcare facility.MethodsSemi‐structured interviews were conducted with patients and families to explore the experience of having a fall. Data were analysed thematically.ResultsThe themes that emerged from the 14 interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(28 reference statements)
0
1
1
Order By: Relevance
“…The inability to mitigate their risk of falling resulted in older people feeling anxious and uncertain about how to undertake tasks, such as toileting safely, and participants stated that they felt deterred from seeking information and assistance. These findings compare to a recent study that interviewed older people who fell in hospital and reported that they experienced inadequate communication, ageism and anxiety about maintaining their dignity, particularly when needing to use the toilet (Kerr, Newman, and Russo 2023). Recent reviews, including a scoping review that included 41 studies from 12 countries, have found that hospitalised older people had limited knowledge about hospital falls risk and their experiences of falls prevention education were inconsistent (Dolan, Slebodnik, and Taylor‐Piliae 2022; Dabkowski et al.…”
Section: Discussioncontrasting
confidence: 53%
“…The inability to mitigate their risk of falling resulted in older people feeling anxious and uncertain about how to undertake tasks, such as toileting safely, and participants stated that they felt deterred from seeking information and assistance. These findings compare to a recent study that interviewed older people who fell in hospital and reported that they experienced inadequate communication, ageism and anxiety about maintaining their dignity, particularly when needing to use the toilet (Kerr, Newman, and Russo 2023). Recent reviews, including a scoping review that included 41 studies from 12 countries, have found that hospitalised older people had limited knowledge about hospital falls risk and their experiences of falls prevention education were inconsistent (Dolan, Slebodnik, and Taylor‐Piliae 2022; Dabkowski et al.…”
Section: Discussioncontrasting
confidence: 53%
“…Participants who had fallen or nearly fallen, as well as those who did not fall while in hospital, reported similar experiences. These findings compare to a recent study conducted in the UK that found older adults who fell in hospital experienced inadequate communication, ageism and anxiety about maintaining their dignity, particularly when needing to use the toilet [41]. An Australian study also found that hospitalised older adults had limited knowledge about hospital falls risk and their experiences of falls prevention education were inconsistent [26].…”
Section: Discussionmentioning
confidence: 68%